Ship shaft segment location and working space analysis based on parallel platform - Lan Junhui; Li Tianyun; Zhu Xiang; Li Weijia (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] The manual lifting mode is often used for the shafting installation at present,for which a lot of manpower and man hours are required to complete the installation and it is not easy to repair and adjust. In order to improve the automation level of the shafting installation, a special six-degree-of-freedom parallel motion platform is designed to realize the intelligent installation of the shafting.[Methods] A sensor-based observation model was established to use the trilateral centroid localization algorithm to locate the shaft segment. The positional conditions of the contact point between the motion platform and the shaft segment were calculated,and the limit position conditions of various working conditions of the motion platform were analyzed to obtain the working space of the shaft segment.[Results] In view of the above,the safety of the working space for installation of the shaft segment can be estimated,and unnecessary damage during assembly work can be effectively avoided,[Conclusions] the study can provide theoretical guidance and technical support for engineering applications.